ANALISIS DAMPAK PEMILU PRESIDEN JOKOWI TERHADAP RETURN SAHAM (Studi Kasus Saham LQ-45 di Bursa Efek Indonesia) - Ayudia Hanung Diniar; Kiryanto Kiryanto (Jurnal Akuntansi Indonesia, 2015)
Election is one of the political events that influence on a country’s economy. Capital market as one of insrumen economy can not be separated from environmental influences, both economic and environmental non-economicenvironment. This study aimed to analyze the reaction of the capital market to market anomaly events in Indonesia, in this case the 2014 Presidential Election. The reaction of the stock market measured by the abnormal return and trading volume activity stock. The population in this study are the companies whose shares are included in the LQ- 45. This study using event study. The results showed that the positive reaction of investors where the 4 days before and 2 days sebelumm July 9 2014 Presidential Election investors reacted positively. These conditions indicate the existence of investor optimism that the elections will be held on July 9, 2014. And an increase in the average volume of stock trading at before and after the presidential elections July 9, 2014.